A comprehensive examination of U.S. laws enacted to reduce alcohol-related crashes among underage drivers. (December 2015) - Romano, Eduardo; Scherer, Michael; Fell, James; Taylor, Eileen
Abstract: Introduction : To effectively address concerns associated with alcohol-related traffic laws, communities must apply comprehensive and well-coordinated interventions that account for as many factors as possible. The goal of the current research article is to examine and evaluate the simultaneous contribution of 20 underage drinking laws and 3 general driving safety laws, while accounting for demographic, economic, and environmental variables. Methods : Annual fatal crash data (1982 to 2010), policies, and demographic, economic, and environmental information were collected and applied to each of the 51 jurisdictions (50 states and the District of Columbia). A structural equation model was fit to estimate the relative contribution of the variables of interest to alcohol-related crashes. Results : As expected, economic factors (e.g., unemployment rate, cost of alcohol) and alcohol outlet density were found highly relevant to the amount of alcohol teens consume and therefore to teens' impaired driving. Policies such as those regulating the age of bartenders, sellers, or servers; social host civil liability laws; dram shop laws; internal possession of alcohol laws; and fake identification laws do not appear to have the same impact on teens' alcohol-related crash ratios as other types of policies such as those regulating alcohol consumption or alcohol outlet density. Conclusions : This effort illustrates the need for comprehensive models of teens' impaired driving. After simultaneously accounting for as many factors as possible, we found that in general (for most communities) further reductions in alcohol-related crashes among teens might be more rapidly achieved from efforts focused on reducing teens' drinking rather than on reducing teens' driving. Future efforts should be made to develop models that represent specific communities. Practical applications : Based on this and community-specific models, simulation programs can be developed to help communities understand and visualize the impact of various policy alternatives. Highlights: Laws and regulations were enacted to decrease teens' alcohol-related crashes. This effort examines the contribution of 20 underage laws to prevent teens' DUI. Policies regulating alcohol consumption and outlet density have the largest impact. Reducing teens' drinking seems more effective than reducing teens' driving. Community-specific models to address specific scenarios are needed.